2018
DOI: 10.1007/s10865-018-9941-8
|View full text |Cite
|
Sign up to set email alerts
|

Mastery, self-esteem, and optimism mediate the link between religiousness and spirituality and postpartum depression

Abstract: Religious and spiritual beliefs and behaviors are powerful influences in the everyday lives of people worldwide and are especially salient for women and families around the birth of a child. A growing body of research indicates that aspects of religiousness and spirituality are associated with mental health including lower risk of postpartum depression, a disorder that affects as many as 1 in 5 women after birth. The mechanisms, however, are not well understood. In this study, psychosocial resources (mastery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
1
23
1
Order By: Relevance
“…This finding is consistent with previous small literature that demonstrated religiousness and spirituality are associated with lower symptoms of depression in mothers during postpartum. [ 39 40 41 ] These results confirm that spirituality is an important source for the prevention of postpartum depression. These results may affirm that spirituality is possibility an important resource for these women to prevent depression or cope with stressful events in the postpartum period.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This finding is consistent with previous small literature that demonstrated religiousness and spirituality are associated with lower symptoms of depression in mothers during postpartum. [ 39 40 41 ] These results confirm that spirituality is an important source for the prevention of postpartum depression. These results may affirm that spirituality is possibility an important resource for these women to prevent depression or cope with stressful events in the postpartum period.…”
Section: Discussionsupporting
confidence: 58%
“…indicated that women with higher religiousness and spirituality have higher levels of mastery, optimism, and self-esteem in the postpartum period. [ 41 ]…”
Section: Introductionmentioning
confidence: 99%
“…In partnered high-income mothers, tangible paternal involvement (e.g., nighttime infant caregiving) is associated with better sleep health (Tikotzky et al 2015 ) and at least one finding in a population of low-income mothers suggests social support is associated with better sleep health (Mersky et al 2020 ). In addition, belonging to a church community, which is more common in rural areas, is associated with lower odds of PPD (Cheadle and Dunkel Schetter 2018 ; Jesse and Swanson 2007 ). However, we know little of the impact of the types of close relationships that are more common in low-income rural populations (Barnett et al 2012 ) that could be protective of sleep health in new mothers (Carroll et al 2019 ).…”
Section: Gaps In the Literature And Recommendations For Future Researmentioning
confidence: 99%
“…Okun and colleagues (2018) demonstrate the role that poor sleep quality plays in predicting postpartum depression symptoms, even after controlling for antenatal mood symptoms. Finally, Cheadle et al (2018) addressed the protective factors underlying the relationship between religiosity and spirituality with lower depressive symptoms in the postpartum. These methodologically strong papers offer a unique perspective on the longitudinal course of depressive symptoms across the perinatal period.…”
Section: Special Issue Highlightsmentioning
confidence: 99%